2017
DOI: 10.1080/14767058.2017.1384457
|View full text |Cite
|
Sign up to set email alerts
|

Significance of assay of nucleated RBCs in umbilical cord blood in neonates with meconium-stained amniotic fluid

Abstract: Our results support previous studies which indicate the presence of meconium can be associated with chronic fetal hypoxia as demonstrated by elevated fetal NRBC levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
3
2
0
Order By: Relevance
“…NRBC's/100 WBCs was highly significantly increased in group 1. Our results were in agreement with study of Elsokkary et al (8) as they reported that there were no statistically significant differences concerning cord blood WBC count and hemoglobin level. However, there were statistically highly significant differences concerning NRBC per mm 3 and NRBC per 100 WBCs with higher values in the MSAF group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…NRBC's/100 WBCs was highly significantly increased in group 1. Our results were in agreement with study of Elsokkary et al (8) as they reported that there were no statistically significant differences concerning cord blood WBC count and hemoglobin level. However, there were statistically highly significant differences concerning NRBC per mm 3 and NRBC per 100 WBCs with higher values in the MSAF group.…”
Section: Discussionsupporting
confidence: 93%
“…There was no significant difference regarding birth weight and sex distribution among the studied groups. In accordance with our results, the study of Elsokkary et al (8) as they included 80 women who were divided into 2 groups: Group I (n=40): included women with meconium-stained amniotic fluid. Group II (n=40): included women with clear liquor.…”
Section: Discussionsupporting
confidence: 75%
“…Elsokkary et al compared the results of forty women with clear amniotic fluid and forty women with meconium-stained amniotic fluid. The mean number of NRBCs in the cord blood of neonates with MSAF was significantly higher than that in the control group, supporting the hypothesis that the presence of meconium may be associated with chronic fetal hypoxia [40].…”
Section: Nrbcs As An Indicator Of Hypoxia Among Neonatessupporting
confidence: 67%
“…As the nucleated red blood cell can be associated with asphyxia or hemolytic disease, this study also verified its correlation with the ABO and RhD incompatibility and presence of variant hemoglobin, trying to exclude situations in which the NRBC is associated with a pathological condition with enhanced erythropoietin activity and does not represent the CBU proliferative condition. 12 , 13 , 14 , 15 …”
Section: Introductionmentioning
confidence: 99%